Causes of death in Brazil - Matheus Ferreira Linares; Silvia Maria Paparotto Lopes; Adriana Eliza Brasil Moreira; Pablo Agustin Vargas; Alan Roger dos Santos Silva; Márcio Ajudarte Lopes (Universidade Estadual de Campinas, 2020)
Aim: In this study we described the causes of mortality in Brazil, its 5 geographic regions, and in the most populated cities of Sao Paulo State in order to contribute for development of prevention and intervention strategies. Methods: Data on causes of death and age distribution of the populations were collected from online public databases and then submitted to the 2001 World Health Organization age standardization of rates for better assessment. Results: Data showed that the main causes of death in Brazil and in all 5 geographic regions were diseases of the circulatory system. Neoplasms were the second most frequent cause of death in Brazil and in 3 regions (South, Southeast and Midwest). However, in the other 2 regions (North and Northeast) the second most common was associated to external causes, being neoplasms the third most often. Additionally, in the South and Southeast the third cause of deaths were from diseases of the respiratory system and from the external causes occupied the fourth position. Analyzing the most populated cities of Sao Paulo State it was observed that all of them have the same profile of the country. On the other hand, as speculated previously, in Piracicaba city, the most common cause of mortality was neoplasm. Conclusions: These findings showed that Brazil has a large spectrum of causes of death and methods to decrease the mortality rates should be implemented in a local scenario rather than a nation-wide approach, where each location has to focus on its most urging problem.